The Legal Framework of Abortion in Indonesia and Its Human Rights Im-plications - Zulvina, Nadifa Fauliza; Sutarno, Sutarno; Pramono, Agung (Institute for Law and Economics Studies, 2025)
Abortion continues to be one of the most contentious problems globally, encompassing sensitive discussions across legal, ethical, and reproductive health aspects. In Indonesia, the issue is particularly critical due to the conflict between upholding the fetus's right to life and ensuring women's reproductive health rights. Recent regulatory changes illustrate this complexity: what was previously a complete prohibition under the former Criminal Code has transformed into conditional permissibility under Law No. 17 of 2023 on Health, Government Regulation No. 28 of 2024 on Reproductive Health, and Minister of Health Regulation No. 2 of 2025. These restrictions are transitional, as abortion will be fully regulated under the new Criminal Code (Law No. 1 of 2023) scheduled to be implemented in 2026. This study utilizes a normative juridical methodology, incorporating statutory and conceptual approaches, to analyze three fundamental issues: the legal status of the fetus, women's reproductive health rights, and the legal protection afforded to physicians conducting conditional abortions. The findings indicate that although the fetus is legally acknowledged as possessing a right to life from conception, these rights may be curtailed in situations such as medical emergencies or pregnancies arising from rape. Simultaneously, women's reproductive health rights are unequivocally secured at both national and international levels. Legal protections for physicians are there; nonetheless, loopholes and ambiguities permit opposing interpretations, so compromising legal certainty.